2019
DOI: 10.1093/mnras/stz3004
|View full text |Cite
|
Sign up to set email alerts
|

Star formation at the Galactic Centre: coevolution of multiple young stellar discs

Abstract: Studies of the Galactic Centre suggest that in-situ star formation may have given rise to the observed stellar population near the central supermassive black hole (SMBH). Direct evidence for a recent starburst is provided by the currently observed young stellar disc (2-7 Myr) in the central 0.5 pc of the Galaxy. This result suggests that star formation in galactic nuclei may occur close to the SMBH and produce initially flattened stellar discs. Here we explore the possible build-up and evolution of nuclear ste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…We will discuss this in the next section. From N-body simulations, Mastrobuono-Battisti & Perets (2013, 2016; Mastrobuono-Battisti et al (2019b) found that the young structures can survive despite being embedded in an older population. Moreover, they are found to rotate faster than the population in which they are embedded.…”
Section: Ymr: Evidence Of In Situ Formationmentioning
confidence: 99%
“…We will discuss this in the next section. From N-body simulations, Mastrobuono-Battisti & Perets (2013, 2016; Mastrobuono-Battisti et al (2019b) found that the young structures can survive despite being embedded in an older population. Moreover, they are found to rotate faster than the population in which they are embedded.…”
Section: Ymr: Evidence Of In Situ Formationmentioning
confidence: 99%
“…The population of S-stars consisting of 2 disks is not relaxed, hence any current configuration is subject to resonant and non-resonant relaxation processes in the nuclear star cluster. The configuration of 2 perpendicular stellar disks can be stable over a timescale of 10 8 years as demonstrated in the simulations by Mastrobuono-Battisti et al (2019) that we refer to later. In the current section we mention key dynamical processes that might have contributed to the X-structure and so far could have influenced it.…”
Section: Basic Dynamical Timescalesmentioning
confidence: 74%
“…The possibility of different coexisting stellar disks in the Galactic Center has also been discussed theoretically by Mastrobuono-Battisti et al (2019). Here, the authors simulate multiple stellar disks in the central stellar cluster.…”
Section: Possible Sources Of Perturbationmentioning
confidence: 99%
“…Tsatsi et al 2017showed that using N-body simulation of inspiralling clusters to the center of the Milky Way can reproduce both the morphological and kinematical properties of the NSC. On the other hand, Mastrobuono-Battisti et al (2019) showed that in the presence of an aspherical, time-variable potential (e.g., due to the presence of a discrete stellar black hole cusp), counter-rotating disks can perturb the dynamics of older stellar populations leading to accelerated relaxation, while the younger populations show a larger amount of rotation. Younger populations always show larger rotation compared to older ones, but the difference is even larger for counter-rotating disks.…”
Section: Kinematics Vs Metallicitymentioning
confidence: 99%